Optimalisasi Literasi Digital Bagi Penyuluh Agama : Upaya Meningkatkan Kemampuan Mengatasi Masalah Sosial - Artanti Laili Zulaiha (Balai Diklat Keagamaan Semarang, 2024)
This research is a descriptive qualitative study, with the aim of finding out the digital literacy of Islamic religious instructors can improve their abilities in overcoming current problems and the application of understanding digital literacy for Islamic religious instructors in overcoming contemporary problems. The research method is descriptive. Data collection methods are questionnaires, observations and interviews. The questionnaire instrument seeks to determine the digital literacy of Islamic religious instructors in overcoming current problems. The observation instrument seeks to obtain data on the digital literacy of Islamic religious instructors in overcoming current problems. The research results show that the digital literacy of Islamic religious instructors can be used as an effort to improve their ability to overcome current problems. Application of digital literacy Islamic religious instructors use an understanding of digital literacy in using the internet and social media when helping people overcome the current problems they face. Based on the research results, the author suggests that Islamic religious instructors at KUA Karanganyar, Purbalingga Regency be able to increase knowledge about digital literacy and actively use the internet and social media in an effort to improve their ability to overcome current problems. Keywords: digital literacy, Islamic religious instructor, current problems.